Canal length evaluation of curved canals by direct digital or conventional radiography - MENTEŞ, ALİ RECAİ (MOSBY, INC, 2002)
Objectives. The purpose of this study was to compare the accuracy of a digital radiograph imaging system (DDR) with conventional radiography for the purpose of estimating endodontic file lengths in curved canals of mandibular molars. Study design. Sixty extracted human mandibular molars with root curvatures ranging from 5degrees to 52degrees were mounted in plastic blocks. Canal length was estimated by using on-screen DDR with both 2- and 3-click measurement and from conventional E-speed radiographs by using a millimeter ruler and x2 magnification. Two operators familiar with both radiographic methods performed the estimates. Results. One-way analysis of variance and Newman-Keuls tests revealed no significant differences between the groups. Although both conventional and DDR methods of analysis overestimated the true canal length, the DDR accuracy improved as the curvature severity increased. Conclusions. The image quality of DDR systems has improved to the point that they can now be used for estimating canal lengths, even for curved canals, with accuracy comparable to that of conventional radiographs. However, further work remains to be done to optimize image quality.
Keywords: ENDODONTIC WORKING LENGTH; SENS-A-RAY; INTRAORAL RADIOGRAPHY; RADIO VISIOGRAPHY; FILE LENGTHS; RADIOVISIOGRAPHY; SYSTEM